Influence of zno nanoparticles ana non-nano zno on survival and reproduction of earthworm and springtail in tropical natural soil - Alves M.L. (2019)
© 2019, Revista Brasileira de Ciencia do Solo. All rights reserved.In recent years, various studies and development using nanoparticles (NPs) have been carried out in the most diverse areas of knowledge. Although nanomaterials are widely employed by many sectors and some may have a fertilizing potential, little is known about their effects on the environment. This study aimed to evaluate the effect of applying, in tropical natural soil, different contents of nanoparticles of zinc oxide (NPs-ZnO) and non-nano zinc oxide (ZnO) on soil pH and on the survival and reproduction rates of earthworms (Eisenia andrei) and springtails (Folsomia candida) through standardized ecotoxicological tests. The tests used a tropical soil representative of Brazil, classified as Entisol (Neossolo Quartzarênico órtico típico) with no history of agricultural use, collected in the 0.00-0.20 m layer, previously sieved (2-mm mesh) and defaunated. The experimental design was completely randomized, and treatments consisted of two forms of zinc (Zn), NPs-ZnO and ZnO, at the following doses: 0, 50, 100, 200, 400, 800, 2,000, and 4,000 mg kg-1. Standardized ecotoxicological tests showed no toxicity of NPs-ZnO in terms of lethality of E. andrei and F. candida. In E. andrei reproduction tests, NPs-ZnO were toxic at doses higher than 400 mg kg-1 (EC50 of 1,021 mg kg-1). Tests with F. candida demonstrated that its reproduction rate was significantly affected by NPs-ZnO at a rate of 4,000 mg kg-1 (EC50 of 3,636 mg kg-1). When used in Entisol, the NPs-ZnO inhibit the reproduction of earthworms and springtails; earthworms are more sensitive to such an effect, it being demonstrate at lower contents than those found for springtails.